Heat-resistant polyester film
The heat-resistant polyester film with a multi-layer structure and specific flake glass content addresses the issues of heat resistance and dimensional stability in PEN films, ensuring reliable performance in flexible circuit board applications.
Patent Information
- Application Number
- JP2023167699
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
Current heat-resistant polyester films, such as polyethylene naphthalate (PEN) films, lack sufficient heat resistance and dimensional stability at high temperatures, leading to potential wrinkling and circuit collapse during soldering in flexible circuit board applications.
A heat-resistant polyester film with a multi-layer structure, comprising an A layer containing flake glass and a B layer, where the A layer has a specific content of flake glass (10-30% by weight) and a thickness of 2.0 μm or less, providing enhanced heat-resistant dimensional stability and mechanical strength at high temperatures.
The film achieves excellent heat-resistant dimensional stability and mechanical strength at high temperatures, along with improved surface properties, enabling reliable performance in flexible circuit board applications without wrinkling or circuit collapse.
Smart Images

Figure 2025057880000001 
Figure 2025057880000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat-resistant stretched film, and more particularly to a heat-resistant polyester film having excellent heat-resistant dimensional stability and mechanical strength at high temperatures and excellent surface properties. [Background technology]
[0002] Thermoplastic polyester films, in particular biaxially oriented films of polyethylene naphthalate (hereinafter sometimes referred to as "PEN") and polyethylene terephthalate (hereinafter sometimes referred to as "PET"), have excellent mechanical properties, heat resistance, and chemical resistance, and are therefore widely used as magnetic tapes, photographic films, packaging films, films for electronic components, electrical insulating films, films for metal lamination, films to be attached to the surfaces of glass displays and the like, films for protecting various components, and films for substrate materials.
[0003] In recent years, with the demand for miniaturization of electric or electronic circuits, the components for these applications have also become smaller and more easily mounted, and further heat resistance is required. In addition, in automotive applications, the range of use has expanded beyond the driver's cab to the engine compartment, and components that are suitable for dimensional stability at higher temperatures are required.
[0004] Among various applications, for example, if we focus on flexible circuit boards, a flexible circuit is made by arranging an electric circuit on a flexible substrate, and is produced by laminating metal foil or plating the film that serves as the substrate, then etching it to form a circuit, heat treating it, mounting circuit components, etc. Conventionally, polyimide (hereinafter sometimes referred to as "PI") films have generally been used as films for flexible circuit boards because of their good adhesion to the circuit and heat resistance during soldering when mounting the circuit components.
[0005] While flexible circuits are required to be smaller and more dense, cheaper materials are also required for circuit board materials. PET film is inexpensive and is used in some places because of its good chemical resistance and insulation properties. However, the heat resistance of the film is not sufficient for recent high-density circuit boards. In addition, lead-free solder has recently been used from the viewpoint of environmental friendliness, and the soldering temperature in the lead-free solder reflow process may be higher than that of conventional flow solder, so the heat resistance of PET film is still insufficient.
[0006] Against this background, plastic films to replace conventional PI and PET films have been sought, and among heat-resistant plastic films, relatively inexpensive polyethylene naphthalate (PEN) films have been considered, with Patent Document 1 proposing, for example, the use of PEN films for flexible circuit boards. However, because PEN films lack the dimensional stability required at high temperatures for the recent high density of circuits, if left as is, the film may wrinkle after soldering in the circuit component mounting process, or the flatness of the circuit may be lost, resulting in unevenness.
[0007] As a method for improving the heat-resistant dimensional stability of a polyethylene naphthalate film, Patent Document 2 discloses a method in which the film is subjected to a thermal relaxation treatment, and Patent Document 3 discloses a method in which the film is fixed in a metal frame and heat-treated for a long period of time. These special film-forming methods have the problem of low productivity, and there is a demand for a polyester film that can be produced by a simpler, more general film-forming method.
[0008] Patent Document 4 describes that by using a PEN film containing short glass fibers, soldering resistance at high temperatures of around 260° C. can be obtained due to the reinforcing effect of the short glass fibers. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Japanese Patent Application Publication No. 62-93991 [Patent Document 2] JP 2001-191405 A [Patent Document 3] JP 2006-316217 A [Patent Document 4] Patent No. 6215690 Summary of the Invention [Problem to be solved by the invention]
[0010] However, for example, when applied to flexible circuit boards, in addition to ensuring heat-resistant dimensional stability and mechanical strength of the film at high temperatures, more recently, due to the use of precision components in the circuit component mounting process, smoothness of the film surface is required to obtain flatness of the circuit during mounting. However, at present, a method for obtaining excellent heat-resistant dimensional stability and mechanical strength of polyethylene naphthalate at high temperatures and surface properties has not yet been provided. In view of the above circumstances, an object of the present invention is to provide a heat-resistant polyester film which is excellent in heat-resistant dimensional stability and mechanical strength at high temperatures and also has an excellent surface property. [Means for solving the problem]
[0011] The present inventors have found that the above problems can be solved by using a specific heat-resistant polyester film, and have completed the present invention.
[0012] That is, the present invention provides the following heat-resistant polyester film.
[0013] [1] A heat-resistant polyester film having an A layer containing glass flakes and at least one B layer, The A layer and the B layer each contain polyethylene naphthalene dicarboxylate as a main component, The content of the glass flakes is 10% by weight or more and 30% by weight or less based on the weight of the polyester film, The thickness of the glass flake is 2.0 μm or less, The heat-resistant polyester film is The storage modulus (E´200) in viscoelasticity measurement at 200°C is 600 MPa or more in the longitudinal direction of the film, The storage modulus (E´260) in viscoelasticity measurement at 260 ° C is 300 MPa or more in the longitudinal direction of the film, A heat-resistant polyester film, wherein the difference ΔE'(200-260) between the storage modulus (E'200) and the storage modulus (E'260) is 300 MPa or less.
[0014] [2] The heat-resistant polyester film according to [1], having the layer B on both sides of the layer A.
[0015] [3] The heat-resistant polyester film according to [1] or [2], wherein the length of the glass flakes is 85 μm or more and 300 μm or less.
[0016] [4] The heat-resistant polyester film according to any one of [1] to [3], which has a melting peak temperature of 266° C. or higher as measured by DSC.
[0017] [5] The heat-resistant polyester film according to any one of [1] to [4], wherein the maximum height Rz of the layer B measured on the surface opposite to the layer A side is 3000 nm or less.
[0018] [6] A flexible printed circuit board comprising the film according to any one of the above items [1] to [5]. Effect of the Invention
[0019] The heat-resistant polyester film of the present invention has the above-mentioned constitution, and can be a heat-resistant stretched film having excellent heat-resistant dimensional stability and mechanical strength at high temperatures and excellent surface properties. Furthermore, when the film of the present invention is used for a flexible printed circuit board, it can provide high productivity in the production of precise practical equipment in the circuit component mounting process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to these embodiments.
[0021] In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits.
[0022] [Polyethylene naphthalene dicarboxylate] The polyethylene naphthalenedicarboxylate constituting the film of the present invention uses naphthalenedicarboxylic acid as the main dicarboxylic acid component and ethylene glycol as the main glycol component. Examples of naphthalenedicarboxylic acid include 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, and 1,5-naphthalenedicarboxylic acid, and among these, 2,6-naphthalenedicarboxylic acid is preferred. Here, "main" means at least 90 mol%, preferably at least 95 mol%, of all repeating units in the polymer constituting the film of the present invention. When polyethylene naphthalene dicarboxylate is a copolymer, a compound having two ester-forming functional groups in the molecule can be used as a copolymerization component constituting the copolymer, and examples of such compounds that can be preferably used include dicarboxylic acids such as oxalic acid, adipic acid, phthalic acid, sebacic acid, dodecane dicarboxylic acid, isophthalic acid, terephthalic acid, 1,4-cyclohexane dicarboxylic acid, 4,4'-diphenyl dicarboxylic acid, phenylindan dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, tetralin dicarboxylic acid, decalin dicarboxylic acid, diphenyl ether dicarboxylic acid, etc., oxycarboxylic acids such as p-oxybenzoic acid, p-oxyethoxybenzoic acid, and dihydric alcohols such as trimethylene glycol, tetramethylene glycol, hexamethylene glycol, cyclohexane methylene glycol, neopentyl glycol, ethylene oxide adducts of bisphenol sulfone, ethylene oxide adducts of bisphenol A, diethylene glycol, and polyethylene oxide glycol. These compounds may be used alone or in combination of two or more. Among these, preferred examples of the acid component include isophthalic acid, terephthalic acid, 4,4'-diphenyldicarboxylic acid, 2,7-naphthalenedicarboxylic acid, and p-oxybenzoic acid, and preferred examples of the glycol component include trimethylene glycol, hexamethylene glycol, neopentyl glycol, and an ethylene oxide adduct of bisphenol sulfone.
[0023] Other polyesters that can be mixed with polyethylene naphthalene dicarboxylate include polyethylene terephthalate, polyethylene isophthalate, polytrimethylene terephthalate, polyethylene-4,4'-tetramethylene diphenyl dicarboxylate, polyethylene-2,7-naphthalene dicarboxylate, polytrimethylene-2,6-naphthalene dicarboxylate, polyneopentylene-2,6-naphthalene dicarboxylate, poly(bis(4-ethyleneoxyphenyl)sulfone)-2,6-naphthalene dicarboxylate, etc. Among these, polyethylene isophthalate, polytrimethylene terephthalate, polytrimethylene-2,6-naphthalene dicarboxylate, and poly(bis(4-ethyleneoxyphenyl)sulfone)-2,6-naphthalene dicarboxylate are preferred. When these other polyesters are further mixed, one type or two or more types may be used in combination.
[0024] Furthermore, the polyethylene naphthalene dicarboxylate of the present invention may be one in which some or all of the terminal hydroxyl groups and / or carboxyl groups have been blocked with a monofunctional compound such as benzoic acid or a methoxypolyalkylene glycol, or may be one which has been copolymerized with a small amount of a trifunctional or higher functional ester-forming compound such as glycerin or pentaerythritol within a range in which a substantially linear polymer is obtained.
[0025] The polyethylene naphthalene dicarboxylate of the present invention can be obtained by a conventionally known method, for example, by directly obtaining a low polymerization degree polyester by reacting a dicarboxylic acid with a glycol, or by reacting a lower alkyl ester of a dicarboxylic acid with a glycol in the presence of an ester exchange catalyst, and then carrying out a polymerization reaction in the presence of a polymerization catalyst.
[0026] The intrinsic viscosity in the present invention is preferably 0.47 to 0.90 dl / g, more preferably 0.50 to 0.80 dl / g. If the intrinsic viscosity is less than 0.47 dl / g, the film becomes brittle and it is difficult to stably form the film. If the intrinsic viscosity of the film exceeds 0.90 dl / g, the intrinsic viscosity of the PEN polymer must be made considerably high, and a long time is required for polymerization in a normal synthesis method, resulting in poor productivity. In order to obtain a polymer with a high intrinsic viscosity, it is preferable to subject polyethylene naphthalene dicarboxylate obtained by a known method to solid-phase polymerization after a normal synthesis method, but this is not preferable because it requires dedicated equipment and increases production costs.
[0027] [Flake-shaped glass] The polyester film of the present invention has a layer A containing glass flakes. The content of the glass flakes in the layer A is 10% by weight to 30% by weight or less, preferably 15% by weight to 27% by weight or less, and more preferably 17% by weight to 25% by weight or less, based on the weight of the polyester film. By the lower limit of the content of the flake glass being within the above range, it is possible to obtain heat-resistant dimensional stability and mechanical strength at high temperatures. Also, if it is equal to or less than the upper limit described in the present invention, it is possible to uniformly disperse the flake glass in the polyester resin, and to obtain good heat-resistant dimensional stability and mechanical strength. Furthermore, it is possible to perform good film stretching, and the film surface can be made smooth, and it is possible to obtain a polyester film suitable for application to flexible circuit boards, etc. The content of the flake glass must be within the above range. When the content is less than 10% by weight and approaches 0% by weight, the heat resistance dimensional stability of the flexible printed circuit board may become insufficient, but the surface smoothness tends to be good. Moreover, if the content exceeds 30% by weight, for example, exceeds 50% by weight, the heat resistance of the film may increase, but on the other hand, the smoothness of the film may become insufficient. Thus, the present inventors have found that there is a trade-off between heat resistant dimensional stability and mechanical strength on the one hand and surface smoothness on the other, which has led to the present invention. Furthermore, because flexible circuits are required to be smaller and have higher density, they must have a good balance of heat resistance, dimensional stability, mechanical strength, and surface smoothness. Therefore, in the present invention, by making the content 10% by weight or more and 30% by weight or less, it is possible to achieve a good balance of heat resistant dimensional stability, mechanical strength, and surface smoothness required for a flexible printed circuit board. Here, 10% by weight to 30% by weight based on the weight of the polyester film means the blending amount of glass flakes relative to 100% by weight of the polyester film composed of a resin component not containing glass flakes.
[0028] The thickness of the glass flakes is 2.0 μm or less, preferably in the range of 0.05 μm to 2 μm, and more preferably in the range of 0.1 μm to 1 μm. Since the thickness of the flake glass is 2.0 μm or less, it can be stretched without using special equipment or conditions for stretching polyester film. In addition, it is possible to prevent the film surface from becoming rough. On the other hand, if the thickness is less than the lower limit, the strength of the glass flakes themselves will decrease, and they may be easily broken and become small when kneaded into a resin, etc. As a result, there is a possibility that the desired heat-resistant dimensional stability and mechanical strength will not be obtained. Depending on the shape of the glass flake, the thickness can also be indicated by the diameter.
[0029] In this specification, the thickness of the flake glass refers to the average thickness. The thickness can be measured by using a known method, for example, by stacking 100 or more flake glass sheets, measuring the thickness of the flake glass laminate using a scanning electron microscope (SEM), and dividing the total thickness by the number of sheets measured. In addition, when the flake glass is contained in the film, the cross section of the film is scraped, and 10 or more flake glass sheets are observed using a scanning electron microscope (SEM), and the thickness is measured and averaged.
[0030] The length of the glass flakes is preferably 85 μm to 300 μm. For example, The length is preferably 100 μm or more and 300 μm or less, and more preferably 100 μm to 250 μm or less. In this specification, the length of the glass flakes refers to the average particle size measured using the following method. The average particle size is the particle size (D50) corresponding to a cumulative mass percentage of 50% in the particle size distribution measured based on the laser diffraction scattering method. When glass flakes are contained in a film, the cross section of the film is scraped, and 10 or more points of the glass flakes are observed using a scanning electron microscope (SEM), and the longest length is measured as the particle size and averaged.
[0031] If the length of the flake glass exceeds the upper limit, it is undesirable because it becomes difficult to stretch the polyester film, the film surface is easily roughened, and application to flexible circuit boards, etc. If the length is less than the lower limit, the strength of the flake glass itself decreases, and it becomes easily broken and small when kneaded into a resin, and although the dispersibility in the film improves, the reinforcing effect in the resin is small, and the desired heat-resistant dimensional stability and mechanical strength cannot be obtained, which is undesirable.
[0032] The composition of the flake glass can be a generally known glass composition. Specifically, glass with a low content of alkali metal oxides, such as E glass, can be suitably used. The composition and manufacturing method of the flake glass are disclosed in the publicly known Japanese Patent Publication No. 7001609 and International Publication No. WO 2006 / 068255.
[0033] In addition to the flake glass of the present invention, any other material may be added in addition to the flake glass, so long as it satisfies the high-temperature storage modulus and surface roughness characteristics specified by the present invention. For example, a fibrous material is suitable. Examples of fibrous materials include short glass fibers such as fibrous carbon fiber and fibrous glass. However, compared with the flake shape of the present invention, the fibrous shape is less likely to be oriented in a planar shape during stretching, so that the heat-resistant reinforcement effect of the film is less likely to be exhibited compared with the flake shape, and the surface property is also more likely to become rough. When a fibrous material is added, the content thereof is less than the content of the flake glass, and more preferably less than 10% by weight.
[0034] [Storage modulus] The heat-resistant polyester film of the present invention has a storage modulus (E'150) in the longitudinal direction of the film as measured by viscoelasticity at 150°C of 1380 MPa or more, more preferably 1400 MPa or more, even more preferably 1700 MPa or more, and particularly preferably 2600 MPa or more. The upper limit of the storage modulus (E'150) does not necessarily have to be determined, but is, for example, 5000 MPa or less, and preferably 4000 MPa or less. If the storage modulus (E'150) is within the above range, a heat resistance reinforcing effect can be obtained.
[0035] The heat-resistant polyester film of the present invention has a storage modulus (E'200) in the longitudinal direction of the film as measured by viscoelasticity at 200°C of 600 MPa or more, more preferably 700 MPa or more, even more preferably 900 MPa or more, and particularly preferably 1300 MPa or more. The upper limit of the storage modulus (E'200) does not necessarily have to be determined, but is, for example, 3000 MPa or less, and preferably 2500 MPa or less. If the storage modulus (E'200) is within the above range, a heat resistance reinforcing effect can be obtained.
[0036] The heat-resistant polyester film of the present invention has a storage modulus (E'260) in the longitudinal direction of the film as measured by viscoelasticity at 260°C of 300 MPa or more, more preferably 450 MPa or more, even more preferably 650 MPa or more, and particularly preferably 900 MPa or more. The storage modulus (E'260) does not necessarily have to be determined, but is, for example, 3000 MPa or less, and preferably 2500 MPa or less. If the storage modulus (E'260) is within the above range, a heat resistance reinforcing effect can be obtained.
[0037] In the heat-resistant polyester film of the present invention, the difference ΔE′(200-260) between the storage modulus (E′200) and the storage modulus (E′260) is 300 MPa or less, more preferably 295 MPa or less, and further preferably 290 MPa or less. The lower limit of ΔE′(200-260) does not necessarily have to be determined, but is, for example, 30 MPa or more, preferably 50 MPa or more. For example, it may be 100 MPa or more. When the value of ΔE′(200-260) is within the above range, a stable heat resistance reinforcing effect can be obtained.
[0038] In the present invention, the A layer and the B layer contain polyethylene naphthalene dicarboxylate as a main component, and further contain a predetermined amount of flake glass of a predetermined size, thereby making it possible to bring the value of ΔE'(200-260) into the above range. Furthermore, in terms of film forming conditions, a biaxially stretched film is preferred, and the longitudinal and transverse stretching ratios are each preferably 2.5 to 5.0 times, more preferably 3.0 to 4.5 times, so that the storage modulus at each temperature can be brought into the above range. In the subsequent heat setting, the heat setting is performed in a temperature range of 250 to 270°C, and the heat setting time in the present invention is preferably 30 to 300 seconds. The film of the present invention can improve the heat resistant dimensional stability and mechanical properties at 260°C, which is close to the melting point of polyester. The details of the method for measuring the storage modulus can be exemplified by the method described in the Examples.
[0039] The heat-resistant polyester film of the present invention is characterized by having high mechanical strength and heat-resistant dimensional stability in the high temperature range from 200° C. or higher to about 260° C. near the melting point, as well as excellent surface properties. The means for achieving this is to contain a specific amount of flake glass of a specific size and to have a multi-layer structure containing polyethylene naphthalene dicarboxylate as the main component.
[0040] [Maximum height of film surface roughness] The heat-resistant polyester film of the present invention preferably has a maximum height of surface roughness of 3000 nm or less, more preferably 2900 nm or less, and further preferably 2800 nm or less. Preferably, in the B layer, the maximum height Rz measured on the surface opposite to the A layer side falls within the above numerical range. If the maximum height of the surface roughness of the present invention exceeds the upper limit, the glass flakes will be more likely to fall off from the film during the film-forming process, and it may become difficult to obtain flatness in the circuit when mounted in the circuit component mounting process. The lower limit of the maximum height of the surface roughness of the present invention is not determined in accordance with the known polyester films, but a value of about 30 nm or more is preferable in terms of winding properties during film formation.
[0041] [Heat shrinkage rate] The heat-resistant film of the present invention has a thermal shrinkage rate of 2.0% or less, preferably 1.5% or less, in both the longitudinal and transverse directions of the film when heat-treated for 10 minutes at 260° C. The smaller the thermal shrinkage rate, the more preferable it is, and is, for example, 0.1% or more.
[0042] [Film melting point] The heat-resistant polyester film of the present invention preferably has a melting point (sometimes referred to as Tm) of 266° C. or higher, which is a melting peak temperature, measured by sealing a 10 mg sample in an aluminum pan for measurement and heating at a rate of 20° C. / min using a differential scanning calorimeter. More preferably, it is 268° C. or higher, and even more preferably, it is 269° C. or higher. There is no particular upper limit to the melting point.
[0043] The heat-resistant polyester film of the present invention can have a higher melting point than conventional polyethylene naphthalene dicarboxylate films by adding glassy flakes. For example, the film is less likely to deform due to high temperatures during soldering at 260°C, so it can be suitably used in applications including soldering at 260°C. If the melting point is below the lower limit, the film may deform or blister due to high temperatures, such as during soldering at 260°C.
[0044] [Layer composition] The heat-resistant polyester film of the present invention is a laminated film having a laminated structure of an A layer containing flake glass and at least one B layer. A three-layer laminated structure having an A layer containing flake glass as a core layer and a B layer on both sides is more preferable because it is easier to obtain surface smoothness and flatness of the circuit in the mounting process. In addition, it is easier to obtain stretchability in the film formation process and mechanical strength. Layer B may contain glass flakes, but an embodiment that does not substantially contain glass flakes is preferable. When layer B does not substantially contain glass flakes, the surface smoothness of the heat-resistant polyester film can be improved. In addition, when the heat-resistant polyester film of the present invention is used as a flexible circuit board, layer B does not substantially contain glass flakes, so that the glass flakes can be prevented from protruding or falling off the film surface when the film is bent, and good flexibility can be exhibited. Furthermore, by providing layer B, not only can surface smoothness be obtained, but stretchability during the film-forming process can be improved, mechanical strength can be obtained, and a heat resistance reinforcing effect can be stably achieved. In the present invention, "substantially free of flake glass" means that flake glass is not intentionally added to layer B during the film formation process. Therefore, it does not deny that flake glass present in layer A penetrates into layer B during the film formation process of the present invention.
[0045] In the thickness of each layer in the laminated structure of the heat-resistant polyester film of the present invention, the thickness ratio of the A layer containing flaky glass to the total thickness of the laminated film is preferably 40 to 98%, more preferably 50 to 96%, and even more preferably 60 to 94%. Most preferably, it is 80 to 92%. If the thickness ratio of the A layer containing flaky glass is less than the lower limit of the range, the content of flaky glass in the laminated film is reduced, and sufficient heat-resistant dimensional stability and mechanical strength cannot be obtained. On the other hand, if it exceeds the upper limit, the content of flaky glass in the laminated film is increased, making it difficult to stretch the film or the film surface is easily roughened, which may make it difficult to apply to flexible circuit boards, etc.
[0046] [Film thickness] The heat-resistant polyester film of the present invention has a thickness of preferably 10 μm or more and 300 μm or less, more preferably 50 to 250 μm, and can be appropriately selected. If the film thickness is less than the lower limit, the insulating performance of the film may be insufficient when used as a flexible circuit board, for example, or the film may not be able to withstand the strength during processing and may deform. On the other hand, if the film thickness exceeds the upper limit, the film may have insufficient bending resistance, and when an external force is applied, the film may crack or may remain in a folded state and not return to its original state.
[0047] [Film manufacturing method] The heat-resistant polyester film of the present invention is preferably a stretched film stretched in at least one direction, and more preferably a biaxially stretched film. Taking a biaxially stretched film as an example, the film production method will be described. The film can be produced by a known sequential biaxial stretching method or a simultaneous biaxial stretching method, and the method is not particularly limited.
[0048] First, the short glass fibers may be added at any stage of the master chip production stage, the resin composition blending stage, or the resin composition being fed into an extruder, or these methods may be combined. In the film-forming method using the successive stretching method, the resin composition is fed to an extruder and formed into a sheet from a T-die. Depending on the number of layers, for example, in the case of two layers, the resin composition for each layer is fed to two different extruders, laminated in a molten state using a feed block, and then formed into a sheet from a T-die. Thereafter, the film is cooled and solidified on a cooling drum with a surface temperature of 10 to 60°C, and then heated, for example, by roll heating or infrared heating, and stretched in the longitudinal direction (longitudinal direction, sometimes referred to as MD direction) to obtain a longitudinally stretched film. The longitudinal stretching temperature is preferably a temperature higher than the glass transition point (Tg) of the composition, and more preferably a temperature 20 to 40°C higher than Tg. The longitudinal stretching ratio may be appropriately adjusted according to the requirements of the application, but is preferably 2.5 times or more and 5.0 times or less, more preferably 3.0 times or more and 4.5 times or less.
[0049] The film is then stretched in the width direction (transverse direction, sometimes referred to as TD direction), and the transverse stretching process is performed while starting from a temperature 20° C. higher than the glass transition point (Tg) of the composition and increasing the temperature to a temperature (20 to 30)° C. lower than the melting point (Tm) of the resin composition. The maximum transverse stretching temperature is preferably a temperature (100 to 40)° C. lower than Tm. The transverse stretching ratio may be appropriately adjusted depending on the requirements of the intended use, but is preferably from 2.5 to 5.0 times, more preferably from 3.0 to 4.5 times. Thereafter, the film is heat-set and heat-relaxed as necessary to obtain a biaxially oriented film, and such treatments are performed while the film is traveling. When heat-setting is performed, the heat-setting treatment is performed in a temperature range of 250 to 270°C, and the heat-setting time in the present invention is preferably 30 to 300 seconds. The film of the present invention can improve the heat-resistant dimensional stability and mechanical properties at 260°C, which is close to the melting point of polyester. The heat-setting time may exceed the upper limit, but it is preferable to heat-set within this range in practice.
[0050] When a coating layer is further provided, a method of coating the layer during the film stretching process can be used. In this case, the coating liquid is preferably used in the form of an aqueous coating liquid. The solid content of the aqueous coating liquid is usually 20% by weight or less, preferably 1 to 10% by weight.
[0051] [Application] The heat-resistant stretched film of the present invention has excellent strength and heat-resistant dimensional stability in the high temperature range from 200° C. to 260° C., which is close to the melting point of the resin, and is a heat-resistant polyester film with excellent surface properties, and therefore can be suitably used as a film for flexible circuit boards. A flexible printed circuit board can be obtained by laminating a metal layer made of copper foil or conductive paste on at least one side of the heat-resistant polyester film of the present invention and forming a fine circuit pattern on the metal layer. EXAMPLES
[0052] Next, the present invention will be specifically described with reference to examples, but the present invention is not limited to the following examples. The physical properties and characteristics in the examples were measured or evaluated by the following methods. In addition, "parts" means "parts by weight."
[0053] Moreover, the measurements and evaluations in the examples were carried out as follows.
[0054] (1) Total film thickness The total film thickness was determined by clamping the film sample between a spindle detector (K107C, manufactured by Anritsu Electric Co., Ltd.) and measuring the thickness at 10 different positions with a digital differential electronic micrometer (K351, manufactured by Anritsu Electric Co., Ltd.), and averaging the values to determine the total film thickness.
[0055] (2) Thickness of each layer The thickness of each layer of the film was measured by cutting the laminated film into a length of 2 mm and a width of 20 mm, fixing it in an embedding capsule, and then embedding it in epoxy resin (Epomount, manufactured by Refinetech Co., Ltd.). The embedded sample was cut perpendicular to the width direction with a microtome (ULTRACUT UCT, manufactured by LEICA), and the thickness of each layer was observed from the cut surface using an optical microscope.
[0056] (3) Storage modulus The film sample was 5 mm wide and 40 mm long, and was measured using a dynamic viscoelasticity measuring device (DMA8000) manufactured by PerkinElmer Co., Ltd., at a frequency of 1 Hz, with the temperature increased at 2°C / min from room temperature to 260°C. The storage modulus at each temperature was calculated from the obtained chart.
[0057] (4) Heat shrinkage rate A film sample was marked at 30 cm intervals, and heat-treated in an oven at 260°C for 10 minutes without applying a load. The interval between the marks was measured after heat treatment, and the heat shrinkage was calculated in the longitudinal direction (MD) and transverse direction (TD) of the film using the following formula (1). Measurements were taken at five points on the sample in each direction, and the average value was used as the heat shrinkage in each direction. Heat shrinkage rate (%) = ((L0-L) / L0) × 100 (1) (In the formula, L0 represents the gauge length before heat treatment, and L represents the gauge length after heat treatment.)
[0058] (5) Film melting point Measurements were performed using a DSC-60 differential scanning calorimeter manufactured by Shimadzu Corporation. A sample amount of 10 mg was sealed in an aluminum pan for measurement, and DSC measurement was performed under a temperature increase condition of 20°C / min to determine the melting peak temperature, which was taken as the melting point (Tm).
[0059] (6) Maximum film height Rz The surface roughness of layer B was measured on the side opposite to layer A of the obtained film by the following method: A sample was cut out to an area of 10 cm lengthwise × 10 cm widthwise, and a white laser interferometer (NEW VIEW8300) manufactured by Zygo was used. A 20x lens was attached to the interferometer, scanning was performed, and the arithmetic mean height and maximum height (μm) were measured. Measurements were performed over a range of 0.82μm in the MD direction and 0.82μm in the width direction on the surface, excluding unmelted material and foreign matter such as dust. Measurements were performed at 10 random points on a 10cm x 10cm sample, and the average value was taken as the maximum height Rz.
[0060] (7) Measurement of thickness and length of flake glass The cross section of the film was cut using a microtome (RM2255, manufactured by Leica) and observed at 400x magnification using a scanning electron microscope (S-4700, manufactured by Hitachi) to measure the thickness and length of the glass flakes.
[0061] (8) Flake glass content The sample was heated at 450°C for 3 hours, and the flake glass content was calculated from the weight before and after heating.
[0062] (9) Solder heat resistance evaluation The film was floated on a molten solder bath and treated at 260°C for 45 seconds, and then removed and the appearance was observed. The appearance was evaluated according to the following criteria. ◎: No change at all ◎○: Very slight wrinkles, but almost no change ○: Some wrinkles are present on the film edge. △: Some wrinkles were observed, but the shape before the test was maintained. ×: The shape before the test was not maintained.
[0063] [Preparation of pellets] P1: Polyethylene-2,6-naphthalenedicarboxylate with an intrinsic viscosity of 0.63 dl / g was obtained. P2: Using a twin-screw extruder, 37.5% by weight (based on 100% by weight of the resin composition) of flake glass with a thickness of 0.7 μm and a length of 160 μm was added to molten P1, and pellets were produced by melt kneading. P3: Using a twin-screw extruder, 30.0% by weight (based on 100% by weight of the resin composition) of flake glass 5.0 μm thick and 500 μm long was added to molten P1, and pellets were produced by melt kneading. P4: Using a twin-screw extruder, 30.0% by weight (based on 100% by weight of the resin composition) of short glass fibers having a diameter of 3 μm and a length of 150 μm was added to molten P1, and pellets were produced by melt kneading. P5: Using a twin-screw extruder, talc particles (GH-7, manufactured by Hayashi Kasei Co., Ltd.) with a diameter of 0.58 μm and a length of 5.8 μm were added to molten P1 so as to make a content of 30.0% by weight (based on 100% by weight of the resin composition), and the mixture was melt-kneaded to prepare pellets.
[0064] Example 1 P1 and P2 were prepared in the composition ratios shown in Table 1 so that the content of flake glass was 25% by weight, and after drying at 170 ° C for 6 hours, they were fed to an extruder heated to 300 ° C (layer A). Only P1 was dried at 170 ° C for 6 hours and then fed to an extruder heated to 300 ° C (layer B). The resin compositions for layers A and B were fed to two extruders, laminated in a molten state using a three-layer feed block, melt-extruded from a die slit, and cooled and solidified on a casting drum to produce an unstretched film. This unstretched film was biaxially stretched in the longitudinal direction (MD direction) and transverse direction (TD direction) under the conditions shown in Table 1, and finally subjected to a heat treatment at 260 ° C for 2 minutes. The film of this example had a high storage modulus at 150 ° C, 200 ° C, and 260 ° C, and also had excellent mechanical properties. In addition, there was no change in the appearance of the film in the solder heat resistance evaluation at 260 ° C.
[0065] [Examples 2 to 10, Comparative Example 2, Comparative Example 4] A polyester film having a thickness of 100 μm was obtained in the same manner as in Example 1, except that the resin composition, the content of the glass flakes, and the stretching ratio were changed as shown in Table 1. The properties of the obtained film were evaluated, and the results are shown in Tables 1 and 2.
[0066] Comparative Example 1 The composition ratio was changed to P1, which does not contain flake glass, and the number of layers was changed to a single layer film. The stretching ratio was also changed as shown in Table 1, and a polyester film with a thickness of 100 μm was produced. In the case of the polyethylene naphthalate film that does not contain flake glass, the storage modulus was low at 150°C, 200°C, and 260°C, and the mechanical properties were reduced. In addition, the film was significantly deformed in the solder heat resistance evaluation at 260°C.
[0067] Comparative Example 3 The content of flake glass alone was set to 34% by weight in the entire polyester film, and the film was laminated in a molten state using a three-layer feed block as shown in Table 1, and then melt-extruded through a die slit and cooled and solidified on a casting drum to produce an unstretched film. An attempt was made to biaxially stretch this unstretched film, but it could not be stretched even at the low stretching ratio conditions shown in Table 1, and breakage occurred during stretching, making it impossible to obtain a biaxially stretched polyester film. Therefore, it was not possible to evaluate the properties of each film.
[0068] Comparative Example 5 The resin composition, the content of glass flakes, and the stretching ratio were changed as shown in Table 1, and an unstretched film was produced as a single-layer film consisting of only layer A without layer B. An attempt was made to biaxially stretch this unstretched film, but it could not be stretched even at the low stretching ratio conditions shown in Table 1, and breakage occurred during stretching, making it impossible to obtain a biaxially stretched polyester film. Therefore, it was not possible to evaluate the properties of each film.
[0069] Comparative Example 6 The resin composition, the content of the flake glass, and the stretching ratio were changed as shown in Table 1, and an unstretched film was produced as a single-layer film of only the A layer without the B layer. This unstretched film was biaxially stretched under the conditions shown in Table 1, and heat-treated in the same manner as in Example 1. A polyester film having a thickness of 100 μm was obtained in the same manner as in Example 1. The properties of the obtained film were evaluated, and the results are shown in Table 2.
[0070] The above formulation and the above results are shown in Tables 1 and 2 below.
[0071] [Table 1]
[0072] [Table 2]
[0073] As can be seen from Table 1, the heat-resistant polyester films of the examples of the present invention were superior in heat-resistant dimensional stability and mechanical strength at high temperatures, and also in surface properties, compared to the films of the comparative examples. On the other hand, in Comparative Example 1, since it did not contain glass flakes, the storage moduli at 200° C. and 260° C. (E′200, E′260) were outside the range of the present invention, and for example, the solder heat resistance evaluation was insufficient. In Comparative Example 2, the content of glass flakes was outside the range of the present invention, and the solder heat resistance evaluation tended to be slightly inferior. In Comparative Example 3, the content of glass flakes exceeded the range of the present invention, and sufficient stretching could not be performed. In Comparative Example 4, the size of the glass flakes was outside the range of the present invention, the solder heat resistance evaluation tended to be slightly inferior, and the surface smoothness of the film was insufficient. In Comparative Example 5, since the film did not have layer B, it was not possible to stretch the film. In Comparative Example 6, the size of the glass flakes was outside the range of the present invention, and the value of the difference in storage elastic modulus in the high temperature region ΔE′ (200-260) and the surface smoothness were insufficient. In Comparative Example 7, since no glass flakes were included, the solder heat resistance evaluation was insufficient and the surface smoothness was insufficient. [Industrial Applicability]
[0074] The present invention relates to a heat-resistant polyester film which is excellent in heat-resistant dimensional stability and mechanical strength at high temperatures, and which is excellent in surface property.
Claims
1. A heat-resistant polyester film having an A layer containing glass flakes and at least one B layer, The A layer and the B layer each contain polyethylene naphthalene dicarboxylate as a main component, The content of the glass flakes is 10% by weight or more and 30% by weight or less based on the weight of the polyester film; The thickness of the glass flake is 2.0 μm or less, The heat-resistant polyester film is The storage modulus (E'200) in a viscoelastic measurement at 200 ° C. is 600 MPa or more in the longitudinal direction of the film; The storage modulus (E'260) in a viscoelastic measurement at 260 ° C. is 300 MPa or more in the longitudinal direction of the film; The difference ΔE′ (200−260) between the storage elastic modulus (E′200) and the storage elastic modulus (E′260) is A heat-resistant polyester film having a strength of 300 MPa or less.
2. The heat-resistant polyester film according to claim 1 , wherein the layer B is provided on both sides of the layer A.
3. 2. The heat-resistant polyester film according to claim 1, wherein the length of the glass flakes is from 85 μm to 300 μm.
4. The heat-resistant polyester film according to claim 1 , wherein the heat-resistant polyester film has a melting peak temperature of 266° C. or higher as measured by DSC.
5. 2. The heat-resistant polyester film according to claim 1, wherein the layer B has a maximum height Rz of 3000 nm or less, measured on a surface opposite to the layer A side.
6. A flexible printed circuit board comprising the film according to any one of claims 1 to 5.
Citation Information
Patent Citations
Window transactor
JP1987015690A
Flexible circuit substrate
JP1987093991A
Biaxially oriented film and its manufacturing method
JP2001191405A
Biaxially oriented polyester film
JP2006316217A